EVALUATION OF THE CELLULYTIC FUNGI ISOLATED FROM AGRICULTURAL WASTES PRODUCING OF BIOETHANOL - & et al., Kubba (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The number of fungal isolated in this research were 48 fungal isolates that isolated from plant, agricultural and animal waste from three different regions outside Baghdad, and three different regions in Baghdad, screening 24 cellulolytic isolates fungi, which were obtained 8 isolated fungi Aspergillus parasiticus, Trichoderma harzanium, Trichoderma viride, Chladosporium ssp, Alternaria ssp, mycelia asterilia (1), Metarhizium spp and mycelia asterilia (2). Capable of producing bio-alcohol with simultaneous saccharification and fermentation without using the yeasts in fermentation methods isolates which recorded the following; 13.547, 10.511, 8.298, 7.951, 6.668, 6.597, 2.455 and 1.256 ppm. respectively. The best optimal conditions for growth were 30ºC and pH 7.